Tradisi Makan Badulang di Rumah Lontiok Kecamatan Kuok Kabupaten Kampar Provinsi Riau - Dwi Sartika; Claudya Puteri; Harti Veronika; Bunga Amrina Rosyada Br Purba; Adrien Halek; Efri Elwando; Elmustian Elmustian (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
The tradition of eating badulang is an important part of the culture of the people of Kampar Regency, especially in Kuok District, Riau Province. This activity involves a group of people together enjoying a meal served on a dulang (large container), as a symbol of togetherness and kinship. This article aims to explore the meaning, process and changes in the implementation of the tradition of eating badulang at Rumah Lontiok, a traditional house that has high historical and cultural value. The method used in writing this article is literature analysis. The results of the analysis show that the tradition of eating badulang is not only a social activity, but also a means of preserving local cultural values, strengthening social relations between residents, and creating a sense of togetherness in society. However, as time goes by, this tradition faces challenges in maintaining its sustainability amidst the current of modernization.